Identification of supporting components for the tourism attractiveness of Munggu village as a coastal tourism destination in Badung regency - Triana, Dwik Suwarnata; Koerniawaty, Francisca Titing; Darsana, I Made (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Munggu Beach is an attractive destination in Bali. With the potential for natural beauty and various activities that can be done around the beach area. The Munggu Beach destination offers a number of tourist attractions, including stunning sea views, spectacular sunsets, and various activities, such as playing beach volleyball, swimming, and water sports activities. To increase the attractiveness of Munggu Beach, four main components need to be considered: tourism attractions, accessibility, facilities and supporting services. This research aims to analyze the potential attraction of Munggu Beach for developing tourism products and improving visitor experiences. This research uses a qualitative descriptive method with an R&D (Research and Development) approach in Munggu Village. The research results found that with good accessibility, various facilities and adequate supporting services, Munggu Beach can become a promising destination and develop as an attractive and diverse tourist destination in Bali. This research provides recommendations for what Munggu Beach managers can do by updating facilities, promoting local culture, and improving environmental cleanliness.